Everyday Science in Action: Training on Simple Research for Enhancing Scientific Literacy among Science Teachers at MA Salafiyah Kajen Pati - Susilawati; Irman Said Prastyo; Hamdan Hadi Kusuma; Ulil Albab; Ulya 'Uyun Latifah (Community Research and Application Journal (CRAJ), 2026)
Scientific literacy is essential for both teachers and students to understand natural phenomena and make informed decisions in daily life. However, many teachers face challenges in implementing research-based approaches to enhance scientific literacy in their classrooms. This community service project aimed to provide training on simple research methods for improving scientific literacy to science, mathematics, and geography teachers at MA Salafiyah Kajen Pati. Conducted on November 19, 2025, the training involved 17 teachers and introduced the PISA (Programme for International Student Assessment) framework for scientific literacy, encompassing four key components: science content knowledge, science processes, application contexts, and scientific attitudes. The training emphasized the concept of "everyday science" - recognizing that scientific principles are embedded in common daily activities such as cooking, walking, bathing, and using technology. Teachers were introduced to simple research approaches using everyday contexts to strengthen students' scientific literacy, covering the four aspects of scientific literacy: science as a body of knowledge, as an investigative tool, as a way of thinking, and as interaction between science, technology, environment, and society. The training demonstrated how teachers can utilize familiar daily activities as contexts for developing students' scientific competencies including identifying scientific questions, collecting evidence, drawing conclusions, and communicating findings. Participants engaged in discussions about implementing context-based learning in their subject areas and designing simple research activities that connect scientific concepts to students' lived experiences. The program successfully equipped teachers with frameworks and strategies for conducting simple research to enhance scientific literacy, emphasizing that science education should extend beyond textbooks and laboratories to encompass real-world applications.